Comparison of convergent beam electron diffraction and annular bright field atomic imaging for GaN polarity determination. Issue 5 (13th December 2016) - Roshko, Alexana; Brubaker, Matt D.; Blanchard, Paul T.; Bertness, Kris A.; Harvey, Todd E.; Geiss, Roy H.; Levin, Igor
Abstract: Abstract : A comparison of two electron microscopy techniques used to determine the polarity of GaN nanowires is presented. The techniques are convergent beam electron diffraction (CBED) in TEM mode and annular bright field (ABF) imaging in aberration corrected STEM mode. Both measurements were made at nominally the same locations on a variety of GaN nanowires. In all cases the two techniques gave the same polarity result. An important aspect of the study was the calibration of the CBED pattern rotation relative to the TEM image. Three different microscopes were used for CBED measurements. For all three instruments there was a substantial rotation of the diffraction pattern (120 or 180°) relative to the image, which, if unaccounted for, would have resulted in incorrect polarity determination. The study also shows that structural defects such as inversion domains can be readily identified by ABF imaging, but may escape identification by CBED. The relative advantages of the two techniques are discussed.